2017
DOI: 10.21873/anticanres.11291
|View full text |Cite
|
Sign up to set email alerts
|

YM155 Reverses Statin Resistance in Renal Cancer by Reducing Expression of Survivin

Abstract: Abstract. Aim: The purpose of the present study was to clarify whether treatment with YM155, a novel small-molecule inhibitor of survivin, reverses statin resistance in statinresistant renal cell cancer (RCC). Materials and Methods:We induced simvastatin resistance in a renal clear cell carcinoma cell line Statins are a family of 3-hydroxy-3-methylglutaryl coenzyme A (HMG CoA) reductase inhibitors that are used to treat hyperlipidemia. Statins have recently been reported to exert anticancer effects on various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Furthermore, YM155 significantly enhanced the antitumor effects of rapamycin in these cells. Additionally, we found that, in the statin-resistant renal cell clear cell carcinoma cell line, Caki-1-StaR, survivin knockdown by siRNA or YM155 significantly reversed simvastatin resistance in vitro (17). These findings prompted us to confirm the effects of survivin inhibition in a CRPC model.…”
Section: Discussionmentioning
confidence: 79%
“…Furthermore, YM155 significantly enhanced the antitumor effects of rapamycin in these cells. Additionally, we found that, in the statin-resistant renal cell clear cell carcinoma cell line, Caki-1-StaR, survivin knockdown by siRNA or YM155 significantly reversed simvastatin resistance in vitro (17). These findings prompted us to confirm the effects of survivin inhibition in a CRPC model.…”
Section: Discussionmentioning
confidence: 79%
“…Several approaches, including the use of the transcriptional inhibitor sepantronium bromide (YM155), have been designed to target survivin (15)(16)(17). However, recent studies have revealed that an improvement in the response rate was not observed when YM155 was added to the combination therapy of carboplatin and paclitaxel for progressive nonsmall cell lung cancer in Phase I/II trials (18).…”
Section: Discussionmentioning
confidence: 99%
“…(22-24) YM-155 has been reported to overcome drug resistance (e.g. statins (16,(25)(26)(27) docetaxel (28)), improve efficacy of diverse therapies including hypericin-mediated photodynamic therapies (29) and on its own merit, induces apoptosis, reduces colony formation, attenuates invasion and growth of xenograft tumors in nude mice (30)(31)(32)(33). While reduction of survivin by YM-155 is believed to be a foremost mechanism of action, other biochemical targets for this drug are continually being reported in the literature.…”
Section: Discussionmentioning
confidence: 99%